Emotional and interpersonal dimensions of health services : enriching the art of care with the science of care - Ferland, Guylaine, 1957-; Moskowitz, Debbie S.; Dubé, Laurette (Published for the McGill Initiative for the Integrative Management of Health in collaboration with Institut universitaire de gériatrie de Montréal by McGill-Queen's University Press, 2003)
Annotation